Counterfeit Culture dalam Perkembangan UMKM: Suatu Kajian Kekayaan Intelektual - Muhammad Deovan Reondy Putra; Hari Sutra Disemadi (KRTHA BHAYANGKARA, 2022)
The development of the economy in Indonesia, as in other countries, always goes hand in hand with increasing purchasing power and a culture of consumerism. Especially in the world of fashion, this is very obvious. Coupled with the development of technology and the ease of getting information, various kinds of fashion trends from anywhere in the world can easily spread to other parts of the world. Indonesia's position as one of the countries with the largest number of social media users in the world has made Indonesia one of the most lucrative markets for business actors in the fashion world. Various kinds of well-known fashion brands can be easily found in everyday life, from economical ones to very expensive ones, also known as luxury brands. But in reality, not all groups of people are able to follow fashion trends that change frequently. The people's inability to buy certain fashion products is exploited by MSME business actors who make a living in the convection industry, by selling fake fashion products or better known as counterfeit. The use of fake fashion products has become a public secret, and the prestige and glamor gained from using these fashion products are no longer felt by those who use genuine or authentic products. This study explores the development of a counterfeit culture that is developing in Indonesia, the social impact and impact on the development of convection SMEs, as well as analyzing the legal elements behind this phenomenon, in accordance with the existing intellectual property law in Indonesia.